Sistem Multipartai dan Ambang Batas Parlemen: Studi Kasus Sistem Presidensial Indonesia dengan Perbandingan terhadap Jerman dan Taiwan - Simatupang, Karmel Hebron (Jurusan Ilmu Politik Universitas Bangka Belitung, 2025)
This study investigates the necessity of parliamentary thresholds in multi-party and presidential systems, with a particular focus on Indonesia. It examines the rationale behind these thresholds and the factors that should determine the optimal threshold within Indonesia's unique political landscape. Employing a qualitative approach and a comprehensive literature review, the study utilizes Mainwaring's framework, which highlights the challenges posed by the combination of a multi-party system and presidentialism, and advocates for reducing the number of parties through appropriate thresholds. The findings suggest that Indonesia's combination of a presidential system and multi-party structure can lead to instability due to potential legislative gridlock. To enhance government efficiency, the study recommends maintaining or raising the current 4% parliamentary threshold and opposes calls to lower it, as this could lead to further fragmentation and inefficiency. Furthermore, the study proposes simplifying the structure of Indonesia's House of Representatives (DPR) into three factions: pro-government, opposition, and independent. By drawing comparisons with Germany and Taiwan’s 5% thresholds and mixed-member proportional representation systems, the study suggests that similar electoral reforms in Indonesia could minimize wasted votes, improve proportional representation, and foster a more stable governance structure.